Spontaneous-Idiopathic Left Anterior Descending Artery Dissection: Is Watchful Waiting Better Than Immediate Stenting?. (4th September 2013) - Arrivi, A.; Bazzucchi, M.; De Paolis, M.; Placanica, A.; Bock, C.; Milici, C.; Boschetti, E.; Dominici, M.
Abstract : Spontaneous coronary artery dissection (SCAD) is a rare, complex disease, nowadays poorly understood yet. The lack of firm recommendations about this issue is a great limitation which makes any therapeutic decision controversial. The case described is that of a young, otherwise healthy woman, who presented with an ostial dissection of the left anterior descending (LAD) artery. Due to patient's stable clinical and hemodynamic parameters, we used a cautious approach based on watchful waiting and medical therapy, postponing stenting in order to achieve a partial vessel reopening with a more comfortable access to PCI.